EXTRA-MUSICAL ELEMENTS OF THE MUSIC FILM KAWYAGITA MANDALA - Susanthi, Nyoman Lia; Payuyasa, I Nyoman; Putra, Ida Bagus Hari Kayana; Budiyana, Ketut Hery (ARTISTIC : International Journal of Creation and Innovation, 2026)
This study examines the extra-musical elements of the music film Kawyagita Mandala, which highlights gong luang as a sacred and increasingly rare Balinese gamelan. The novelty of this research lies in conceptualizing extra-musical elements not merely as cultural background, but as structuring principles that shape cinematic form. Data were collected using a qualitative descriptive method through interviews with karawitan experts and the production team, supported by a literature review and observation. The findings identify four interrelated dimensions: tattwa (philosophy), susila (ethics), lango (aesthetics), and gegebug (technique), which guide the film’s mise-en-scène, cinematography, montage, and sound. Tattwa dictates ritual-based visual construction; susila regulates ethical production practices; lango shapes visual and sonic harmony; and gegebug reflects reconstructed performance techniques at Apuan Singapadu Studio. By framing these elements as cinematic structures, the study offers a novel perspective on translating sacred musical ontology into contemporary audiovisual practice while supporting cultural preservation.